2009
DOI: 10.1128/aem.00291-09
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Relative Effects of Temperature, pH, and Water Activity on Inactivation of Escherichia coli in Fermented Meat by Meta-Analysis

Abstract: Outbreaks of Escherichia coli infections linked to fermented meats have prompted much research into the kinetics of E. coli inactivation during fermented meat manufacture. A meta-analysis of data from 44 independent studies was undertaken that allowed the relative influences of pH, water activity (a w ), and temperature on E. coli survival during fermented meat processing to be investigated. Data were reevaluated to determine rates of inactivation, providing 484 rate data points with various pH (2.8 to 6.14), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
34
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 51 publications
7
34
1
Order By: Relevance
“…The study indicated that temperature (fermentation, maturation, and storage) accounted for 61% of the variability in the data while pH and accounted for less than 8% [225]. Similarly, in a meta-analysis including 13 studies on inactivation of L. monocytogenes in fermented sausages, temperature explained 60% of the data variability while pH and explained only a small part [226].…”
Section: Reductions Of Pathogens Through Changes In Recipe Andmentioning
confidence: 99%
See 2 more Smart Citations
“…The study indicated that temperature (fermentation, maturation, and storage) accounted for 61% of the variability in the data while pH and accounted for less than 8% [225]. Similarly, in a meta-analysis including 13 studies on inactivation of L. monocytogenes in fermented sausages, temperature explained 60% of the data variability while pH and explained only a small part [226].…”
Section: Reductions Of Pathogens Through Changes In Recipe Andmentioning
confidence: 99%
“…Increased inactivation of relevant pathogens, including VTEC, L. monocytogenes, and Salmonella, with increasing temperatures has been shown in several studies [102,103,222,[225][226][227]. For effective inactivation of pathogens it is crucial to obtain conditions preventing pathogen growth (low pH, ), but once these conditions have been reached, it is the factors of time and temperature that most dramatically improve the microbial safety of the product.…”
Section: Reductions Of Pathogens Through Changes In Recipe Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, with meta-analysis, it is also possible to explain differences in the study outcomes by coding study characteristics, such as: research design features, data collection procedures, type of samples or even year (Hox & De Leeuw, 2003). In the past few years, meta-analysis has increasingly been applied in food safety (Den Besten & Zwietering, 2012;Gonzales Barron, Bergin, & Butler, 2008;Gonzales-Barron & Butler, 2011;Gonzales-Barron et al, 2013;Grieg et al, 2012;McQuestin, Shadbolt, & Ross, 2009;Sánchez, Dohoo, Christensen, & Rajic, 2007). In food safety research, meta-analysis may be conducted to address a broad range of research questions such as disease incidence, prevalence of microorganisms in foods, effect of interventions pre-and postharvest, risk ranking of pathogens and consumer practices, among others.…”
Section: Introductionmentioning
confidence: 99%
“…coli O157:H7 has been modeled as a function of changes in the medium due to the metabolic activity of the starter culture and yeast during fermentation in olives (31) and as a function of pH and water activity (a w ) in soudjouk-style fermented sausages during the process of fermentation and drying (32). The publically available software THERM predicts the growth or lack of growth of E. coli O157:H7 and other pathogens as a function of the timetemperature history of raw-meat products (33); more specifically, tools implementing models to predict the inactivation of E. coli O157:H7 in raw meat (19) and in fermented meat products (34,35) are available from the Australia Food Safety Center of Excellence. However, predicting the response of VTEC throughout the range of conditions that comprise growth and no-growth environments characteristic to FRMS manufacturing and storage has not been approached yet.…”
mentioning
confidence: 99%